Factors associated with the risk of caries development after comprehensive dental rehabilitation under general anesthesia - Yai-Tin Lin; Yng-Tzer J. Lin (Elsevier, 2016)
Background/purpose: The aims of this cross-sectional study were to determine the possible risk factors of caries development in children with early childhood caries (ECC) and to perform a caries risk assessment using Cariogram over a 12-month period. There is no report in examining caries risk assessment under 6 years old children in Taiwan. Materials and methods: Seventy-nine children (mean age 48.80 ± 10.71 months) with ECC indicated for comprehensive dental reconstruction under general anesthesia were selected. A questionnaire was completed by the parents to assess the possible caries-related factors at a 12-month follow-up. Data were collected for caries index, plaque index, Streptococcus mutans (SM) and Lactobacillus (LB) counts, and salivary buffering capacity at the initial examination and at the 12-month follow-up. Children were divided into two groups: caries-free (decayed, extracted, and filled teeth = 0) and caries-recurrent (decayed, extracted, and filled teeth > 0). The children's caries risk was assessed using the Cariogram software program. Results: At the 12-month follow-up, 79.7% of the children had developed new caries. No significant differences were found in parents' education levels, child's oral health practices, or parental knowledge and attitudes toward oral health (P > 0.05) between the caries-free group and the caries-recurrent group. The SM count (P = 0.001) and caries risk assessment (CRA) score (P < 0.001) were found to be significantly associated with new caries development. Conclusion: This study has shown that SM count and CRA score were associated with new caries development in ECC children who needed to be treated under general anesthesia. The modified Cariogram used in this study is another significant tool for predicting new carries development in this particular population.